ANALISIS FAKTOR-FAKTOR DAN STRATEGI PENCEGAHAN BULLYING DI MI NURUL ILMI KOTA BIMA - Rahmah, Lutfia; Masitha, Dewi; Anhar, Ade S. (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
Children represent the nation's most valuable asset and serve as the next generation entrusted with carrying forward national ideals. As such, every child is entitled to the right to life, growth, and development, the right to participate actively in society, and protection from violence, discrimination, and violations of their civil rights and freedoms.When acts of violence or bullying occur within the school setting, they can lead to deep emotional consequences such as resentment, hatred, fear, and a diminished sense of self-worth. Students may develop fear or animosity toward their teachers, younger students may grow to resent and harbor grudges against their seniors, and unhealthy rivalries and conflicts can emerge among peers.The sociology of law is a field of study that explores the dynamic, reciprocal relationship between legal systems and the society in which they operate. It aims to analyze, interpret, and explain legal issues using an empirical and analytical lens, placing them within the broader context of social phenomena. From this perspective, legal norms established by the state are not the only standards of behavior; in practice, societies often adhere more strongly to unwritten social rules and norms.Sociologically, all forms of violence are viewed as abusive actions. Therefore, proactive and consistent efforts are essential to prevent violence and bullying in schools, in order to stop these behaviors from becoming persistent and normalized within the educational environment. ABSTRAK Anak merupakan aset berharga bagi masa depan bangsa dan generasi penerus cita-cita nasional. Oleh karena itu, setiap anak memiliki hak atas kelangsungan hidup, tumbuh kembang secara optimal, berpartisipasi dalam kehidupan sosial, serta mendapatkan perlindungan dari segala bentuk kekerasan, termasuk perlindungan atas hak-hak sipil dan kebebasan individu.Tindakan kekerasan atau bullying yang terjadi di lingkungan sekolah dapat menimbulkan dampak psikologis yang serius, seperti perasaan dendam, kebencian, ketakutan, serta hilangnya rasa percaya diri. Akibat dari kekerasan tersebut, peserta didik bisa saja mengembangkan rasa takut terhadap guru, adik kelas merasa tertekan oleh kakak kelas, dan terjadi konflik atau persaingan yang tidak sehat antar siswa.Sosiologi hukum merupakan cabang ilmu yang membahas hubungan timbal balik antara sistem hukum dan dinamika masyarakat. Disiplin ini berperan dalam memahami serta menjelaskan berbagai persoalan hukum melalui pendekatan yang bersifat empiris dan analitis, dengan melihatnya sebagai bagian dari fenomena sosial. Perspektif sosiologi hukum menunjukkan bahwa hukum formal negara bukan satu-satunya pedoman perilaku, sebab masyarakat sering kali lebih mematuhi norma-norma sosial yang berlaku secara tidak tertulis.Dalam pandangan sosiologis, segala bentuk kekerasan dipandang sebagai bentuk pelecehan. Oleh karena itu, diperlukan upaya pencegahan yang serius terhadap tindakan kekerasan atau bullying di lingkungan sekolah agar peristiwa serupa tidak terus berulang dan membudaya.